2004
DOI: 10.1111/j.1399-3011.2004.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of a laccase from Stachybotrys chartarum covalently linked to a carotenoid‐binding peptide

Abstract: Atwo-step targeting strategy was used to identify improved laccases for bleaching carotenoid-containing stains on fabric. We first applied a modified phage display technique to identify peptide sequences capable of binding specifically to carotenoid stains and not to fabric. Prior deselection on the support on which the carotenoid was localized, increased stringency during the biopanning target selection process, and analysis of the phage peptides' binding to the target after acid elution and polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…It is worth mentioning that laccase was the sole LME produced in shaken cultures, regardless of the isolate and of the added compound or lignocellulosic waste. From data in the literature, laccase production is a prerogative of the genera to which the selected isolates belong (4,23,29). All of the selected isolates were able to colonize the amended ACNA soil under nonsterile conditions, thus showing good tolerance to high concentrations of toxic contaminants and the ability to compete with the indigenous bacterial microflora.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that laccase was the sole LME produced in shaken cultures, regardless of the isolate and of the added compound or lignocellulosic waste. From data in the literature, laccase production is a prerogative of the genera to which the selected isolates belong (4,23,29). All of the selected isolates were able to colonize the amended ACNA soil under nonsterile conditions, thus showing good tolerance to high concentrations of toxic contaminants and the ability to compete with the indigenous bacterial microflora.…”
Section: Discussionmentioning
confidence: 99%
“…Laccases described in recent publications (Moreno et al, 2013;Ryu et al, 2013), are proposed to assist in the pretreatment of biomass by catalyzing the removal of inhibitors in lignocellulosic slurries, but the suggested applications of laccases range from paper and pulp bleaching (Galli et al, 2011), detergent and textile applications (bleaching purposes; Janssen et al, 2004), gelation and emulsion stabilization of food systems (Zaidel et al, 2012(Zaidel et al, , 2013, bioremediation (Galli et al, 2011) and even biomedical applications have been proposed in connection with development of a laccase tolerant to human blood components (Maté et al, 2013). Moreover, as described already 20-25 years ago, laccases can increase water-soluble degradation products by catalysis of ring opening of low molecular weight phenolic lignin model compounds (Kawai et al, 1988) as well as catalysis of C-C bond cleavage of ''synthetic lignin'' substances (Iimura et al, 1995).…”
Section: What Is a Good Laccase? Desirable Features Of An Industrial mentioning
confidence: 99%
“…This enzyme oxidized the artificial substrate ABTS (2,2-azino-di-(3-ethylbenzthiazolinsulfonate) [ 42 ]. Further, Janssen et al stated that the insertion of the peptide sequences IERSAPATAPPP, YGYLPSR, SLLNATK, KASAPAL, and CKASAPALC inserted in the C-terminal of S. chartarum laccase by recombinant DNA tools resulted in laccase- peptide fusions that selectively targeted carotenoid stains and displayed enhanced bleaching potential on stained fabrics [ 43 ]. This suggested that the modification of certain enzymes could improve their activity, suggesting a new area of research in this fungus.…”
Section: S Chartarum Enzymes and Their Possible Applicationsmentioning
confidence: 99%